Deformation behaviour of a low carbon high Mn TWIP/TRIP steel. Issue 12 (13th August 2019) - Tewary, N. K.; Ghosh, S. K.; Chakrabarti, D.; Chatterjee, S.
ABSTRACT: TWIP and TRIP phenomena have been observed in Fe–20Mn–2.5Si–0.3Al–0.06C (wt-%) steel during cold deformation (CD). Mostly austenite, annealing twins and stacking faults are observed in hot rolled solution treated (HRACST) samples. Cold deformation results in γ→ϵ→α′ transformation due to its low stacking fault energy (18 mJ m −2 ). 50CD (50% CD) sample reveals strong Goss, Brass and weak Copper Twin texture components due to slipping and micro-twinning. Maximum ductility of 62% with lower tensile strength is perceived in HRACST sample, whereas, 30CD sample shows excellent tensile strength (1039 MPa) with a lower ductility (23%). Premature failure in 50CD samples is related to the formation of α′-martensite (≈35%) and deformation twins along with a higher strain hardening due to low Al content.